2002
DOI: 10.1172/jci200215506
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of phosphodiesterase 4D in mice shortens α2-adrenoceptor–mediated anesthesia, a behavioral correlate of emesis

Abstract: IntroductionCyclic nucleotides cAMP and cGMP are degraded by at least 11 families of phosphodiesterases (PDEs 1-11) classified according to their gene sequence, substrate specificity, biochemical regulation, and sensitivity to inhibitors (1, 2). The cAMP-specific PDE4 has attracted considerable attention for the treatment of airway inflammatory diseases, since its inhibition results in attenuated inflammatory responses (1,3,4). However, the therapeutic potential of PDE4 inhibitors has been limited by the side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…Interestingly enough, while PDE4 has been shown to be critical in the inflammatory response, the isoform PDE4B specifically has been shown to be critical for LPS-activation of TNF-α. In the same study, PDE4D knockout mice were shown not affect the TNF-α levels (Robichaud et al 2002). However, the specific role of PDE4D and its effects on outcomes in the septic response has yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly enough, while PDE4 has been shown to be critical in the inflammatory response, the isoform PDE4B specifically has been shown to be critical for LPS-activation of TNF-α. In the same study, PDE4D knockout mice were shown not affect the TNF-α levels (Robichaud et al 2002). However, the specific role of PDE4D and its effects on outcomes in the septic response has yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 90%
“…In human circulating monocytes, inhibition of PDE4 by rolipram markedly suppresses TNF-α synthesis and release in response to LPS (Torphy 1998). Inhibition of the PDE4 enzyme has been shown to correlate with decreased TNF-α release from LPS-stimulated whole blood, a cellular marker of nonselective PDE4 inhibition (Muise et al 2002; Robichaud et al 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Based on the work of Robichaud et al ., PDE4D has been viewed as the emetic target of PDE4 inhibitors30. Therefore much effort has been made by medicinal chemists to develop allosteric inhibitors that are able to target specific subtypes which differ in their amino acid sequences in the regulatory domains.…”
Section: Discussionmentioning
confidence: 99%
“…D159687 targets the dimeric form of PDE4D and is sensitive to the PKA phosphorylation activation state of the enzyme through which it appears to achieve improved tolerability22. A-33 targets the monomeric form of PDE4B and achieves improved tolerability by sparing inhibition of PDE4D as PDE4D is thought to be the emetogenic target162330.…”
Section: Discussionmentioning
confidence: 99%
“…Among PDE4 subtypes, PDE4B is a possible target for rolipram, because the inhibition of conditioned avoidance responding by rolipram was attenuated in PDE4B knock-out mice (Siuciak et al, 2007, 2008). Because the nonselective PDE4 inhibitors including rolipram are known to induce the side effect of nausea and vomiting possibly via inhibition of PDE4D (Robichaud et al, 2002), the development of a PDE4B-selective inhibitor may be necessary for clinical trials in the treatment of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%